2018
DOI: 10.1364/boe.10.000066
|View full text |Cite
|
Sign up to set email alerts
|

Cellular-scale evaluation of induced photoreceptor degeneration in the living primate eye

Abstract: Progress is needed in developing animal models of photoreceptor degeneration and evaluating such models with longitudinal, noninvasive techniques. We employ confocal scanning laser ophthalmoscopy, optical coherence tomography (OCT) and high-resolution retinal imaging to noninvasively observe the retina of non-human primates with induced photoreceptor degeneration. Photoreceptors were imaged at the single-cell scale in three modalities of adaptive optics scanning light ophthalmoscopy: traditional confocal refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
3
9
0
Order By: Relevance
“…The eye was enucleated and the tissue postfixed and dehydrated before plastic embedding and sectioning into 2.5 μm sections. Full details of the protocol can be found in Walters et al 23 . A two part hematoxylin and eosin stain was performed to label nuclei blue and cytoplasm pink, allowing assessment of structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…The eye was enucleated and the tissue postfixed and dehydrated before plastic embedding and sectioning into 2.5 μm sections. Full details of the protocol can be found in Walters et al 23 . A two part hematoxylin and eosin stain was performed to label nuclei blue and cytoplasm pink, allowing assessment of structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…TPEF imaging was conducted after the laser exposure for functional measurement of the visual cycle in photoreceptors as described elsewhere. 24 , 25 Briefly, a Ti:Sapphire femtosecond laser (55 fs, 80 MHz, 730 nm, Mai Tai XF-1 with DeepSee attachment; Spectra-Physics, Santa Clara, CA, USA), compensated for second-order dispersion arising from both the optics of the AOSLO and the eye, was used to excite TPEF; the maximum power at the cornea was 3.5 to 4.5 mW. An 840-nm superluminescent diode was used for wavefront sensing with a Shack-Hartmann wavefront sensor, and a maximum power of 45 µW was incident on the cornea.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the 730-nm reflectance channel was used for nonconfocal multioffset imaging, which has been described elsewhere. 25 A third PMT for TPEF imaging (excitation: 730 nm; detection: 400–550 nm) was used. The TPEF time course data was adapted using a method described elsewhere 26 with an exponential function y = Δ F / F e − t / t + 1, where τ is the time constant of TPEF increase and Δ F / F is the relative increase in TPEF.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging the visual cycle may be useful in quantifying photoreceptor function, as demonstrated in three macaque models of altered outer retinal function. In a macaque model of induced retinal degeneration, photoreceptors missing their outer segments showed little change in TPEF upon stimulation (Walters et al 2019) Similarly, phototoxic damage to select cones may be identified by a cell-specific decrease in TPEF intensity and altered TPEF time course after visual stimulation (Schwarz et al 2018). The rate at which TPEF intensity changes with visual stimulation is also slowed in the cones of macaques breathing 10% versus 100% O 2 .…”
Section: Imaging the Visual Cyclementioning
confidence: 97%